FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN IMUNISASI TT PADA WANITA USIA SUBUR (WUS) DI PUSKESMAS KESUMADADI KECAMATAN BEKRI LAMPUNG TENGAH TAHUN 2012 - Mindo Lupiani; Holidy Ilyas; Kunthi Oktiani (Holistik Jurnal Kesehatan, 2019)
ABSTRACT : THE PARENT EDUCATION, ATTITUDE, IMMUNISATION STATUS OF CHILDREN, FAMILY INCOME AND NUTRITIONAL STATUS OF GROUPS OF CHILDREN UNDER THE AGE OF 5 YEARS AT BERINGIN JAYA KEMILING BANDAR LAMPUNG Background : Nutritional status is the expression of a balanced state in the form of a particular variable, or the embodiment of nutriture in a particular form. Prevalence of stunting nutrition problem in Indonesia is still high, that is equal to 37,2%. Prevalence Bandar Lampung city is 44.6% and Kemiling District is 39.6%. Purpose :The purpose of this study is to determine the risk factors associated with nutritional status of children. Methods: This study used cross sectional design. The population of 671 infants with the sample of research that used as many as 88 balita. The sample technique uses cluster sampling technique. Data collection using questioner, height is measured directly and calculate the age of toddler. The child's nutritional status is then measured based on the TB / U index. In this study also examined the relationship of immunization status, maternal education, mother attitude and family income with nutritional status of children. Data analysis with chi square test. This research was conducted at Beringin Jaya, Kemiling Sub District in March 2017. Results: The study showed normal toddler's nutritional status of 78.4% and short-term nutritional status of 21.6%. The result of bivariate analysis showed that variables related to nutritional status were mother's attitude (p = 0,003) and family income (p = 0,032). While unrelated variables namely the status of immunization (p = 0.380) and maternal education (p = 0.249). In accordance with the results of the study, it is advisable that families with low incomes should be upgraded to be able to choose and buy food at cheap prices with good nutrition and quality so that the nutrition of children is sufficient.Pendahuluan: Status gizi adalah ekspresi dari keadaan seimbang dalam bentuk variabel tertentu, atau perwujudan dari nutriture dalam bentuk tertentu. Prevalensi masalah gizi stunting di Indonesia masih tinggi, yaitu sebesar 37,2%. Prevalensi di kota Bandar Lampung sebesar 44,6% dan di Kecamatan Kemiling sebesar 39,6%.Tujuan : Tujuan penelitian ini adalah mengetahui faktor resiko yang berhubungan dengan status gizi  balita.Metode: Penelitian ini menggunakan rancangan cross sectional. Populasi sebanyak 671 balita dengan sampel penelitian yang digunakan sebanyak 88 balita. Teknik sampel menggunakan teknik cluster sampling. Pengumpulan data dengan menggunakan kuesioner, tinggi badan diuukur secara langsung dan menghitung usia  balita. Status gizi anak kemudian diukur berdasarkan indeks TB/U. Dalam penelitian ini juga diteliti hubungan status imunisasi, pendidikan ibu, sikap ibu dan pendapatan keluarga dengan status gizi balita. Analisis data dengan uji chi square. Penelitian ini dilakukan di Kelurahan Beringin Jaya, Kecamatan Kemiling pada bulan Maret 2017.Hasil: penelitian menunjukkan status gizi balita normal sebanyak 78,4% dan status gizi balita pendek sebanyak 21,6%. Hasil analisis bivariat menunjukkan variabel yang berhubungan dengan status gizi yakni sikap ibu (p= 0,003) dan pendapatan keluarga (p= 0,032). Sedangkan variabel yang tidak berhubungan  yakni status imunisasi (p= 0,380) dan pendidikan ibu (p= 0,249). Sesuai hasil penelitian,disarankan keluarga dengan pendapatan rendah perlu ditingkatkan kemampuannya agar dapat memilih dan membeli  makanan dengan harga murah dengan nilai gizi dan kualitas yang baik agar gizi balita tercukupi.